Ubiquitous spin freezing in the superconducting state of UTe2 - Shyam Sundar; Nasrin Azari; Mariah R. Goeks; Shayan Gheidi; Mae Abedi; Michael Yakovlev; Sarah R. Dunsiger; John M. Wilkinson; Stephen J. Blundell; Tristin E. Metz; Ian M. Hayes; Shanta R. Saha; et al. (Communications Physics, 2023)
UTe2 receives significant attention as it may be an example of a spin-triplet superconductor but many features of this material are still to be fully understood. Here, the authors use muon spin rotation to investigate the existence of low-temperature magnetic clusters in single crystals of UTe2 and discuss the potential relationship with the temperature dependent behaviour of the specific heat.